Coordinated frequency regulation among asynchronous AC grids with an MTDC system. (March 2021) - Xiao, Huangqing; Sun, Kaiqi; Pan, Jiuping; Xiao, Liang; Gan, Chun; Liu, Yilu
Highlights: A coordinated frequency regulation scheme for asynchronous AC grids is proposed. The proposed scheme is a communication-free method. A sample and hold component is implemented to enhance the inertia response. A frequency safety control is proposed to improve the system security. Two measures are used to reduce the coupling effect among asynchronous AC grids. Abstract: With the increasing penetration level of renewable power, the power systems' inertias are decreasing. To ensure that the frequency is above the threshold of the under frequency load shedding, one effective way is to share the spinning reserves among asynchronous AC grids through HVDC systems. In this paper, a coordinated frequency regulation scheme that enables spinning reserves sharing is proposed for such hybrid AC/DC grids. This scheme is a communication-free method that consists of the droop control, the inertia emulation control and the frequency safety control. The combined response of the three controls can increase not only the frequency nadir but also the settled frequency of the disturbed grid. In addition, the hysteresis comparators and the power injection limits are adopted in the frequency regulation scheme to reduce the coupling effect among AC grids. Thus, under small and harmless disturbance, the frequency regulation scheme will be inactive; the disturbance in strong AC grids would not affect the weak AC systems. The frequency regulation scheme coordinates well with the automatic generation control of the grids. The feasibility and effectiveness of the proposed frequency regulation scheme are verified through simulation studies.